The relative importance of math‐ and music‐related cognitive and affective factors in predicting undergraduate music theory achievement. Issue 5 (10th April 2019) - Barroso, Connie; Ganley, Colleen M.; Hart, Sara A.; Rogers, Nancy; Clendinning, Jane P.
Summary: Based on research identifying relations between math and music, we aimed to identify the group of cognitive and affective factors related to math and music theory that best explained undergraduate music theory achievement. Using dominance analysis, we predicted the music theory course grades of 230 undergraduate music majors. Potential predictors were narrowed from measures of knowledge, aptitude, experience, confidence, and anxiety in both music theory and math as well as spatial skills and reading test scores. Results suggested that ACT math scores and music theory confidence were important predictors for Music Theories I and II grades. Music Theory I was also predicted by aptitude‐based music theory skills, and Music Theory II was also predicted by math course experience. These findings provide evidence for a relation between math and music theory and support the use of several readily available measures for college‐level music instructors to identify students who may struggle in music theory.